Understanding farm typology for targeting agricultural development in mixed crop-livestock farming systems of Ethiopia - Eshetae, Meron Awoke; Wuletawu, Abera; Tamene, Lulseged D.; Mulatu, Kalkidan; Tesfaye, Abonesh (2023)
Capturing the heterogeneity of farming systems through farm typology is essential for targeting agricultural interventions in a mixed crop-livestock farming system. Therefore, this study aims to construct farm typology in the Doyogena and Basona districts of the Southern and Northern parts of Ethiopia, respectively. A combination of principal component analysis (PCA) and hierarchical clustering (HC) was used to develop generalized and context-specific farm typologies in the study areas using 503 farm household survey data. A generalized farm typology was constructed considering all the variables of the dataset, whereas a context-specific farm typology was developed once all the variables of the data were categorized into three groups: variables that describe i) the resource endowment, ii) technology used, and iii) food and nutrition characteristics of the farm. In both districts, the results of the generalized farm typologies are more generic and are not able to fully capture the diversity of farmers’ resource endowment and food and nutrition security status. Compared to the generalized typologies, context-specific farm typologies are more useful for targeting tailored agricultural development interventions. The context-specific farm typology results show that medium resource endowment with medium income is the dominant farm typology in Basona district whereas low resource endowment with low income is the dominant one in Doyogena district. In terms of technology, the dominant farm typology is medium technology-based farm typology in both districts. Farm typologies constructed based on food and nutrition indicators show that marginal food and nutrition security is the predominant farm typology in Doyogena district but low food and nutrition security is the common one in Basona district. The findings of this study provide several insights into targeting and scaling context-specific agricultural development interventions that can be applicable for sustainable intensification of mixed farming systems.